The emergence of age-related changes in recognition memory in healthy middle-aged adults using the CVLT-II. Issue 6 (1st November 2020) - Williams, Mckenna E.; Graves, Lisa V.; Van Etten, Emily J.; Holden, Heather M.; Delano-Wood, Lisa; Bondi, Mark W.; Corey-Bloom, Jody; Delis, Dean C.; Gilbert, Paul E.
ABSTRACT: Although age-related memory differences between young and older adults have been well documented, fewer studies have investigated memory changes in middle age. We examined the performance of healthy middle-aged adults (40–55 years of age; n = 32) in relation to healthy young (18–25 years of age; n = 57) and older adults (65+ years of age; n = 55) on variations of recognition discriminability (RD) indices derived from the California Verbal Learning Test-Second Edition (CVLT-II). Middle-aged adults performed significantly worse ( p s < .05) than young adults on multiple RD indices that incorporate semantically related distractor items, suggesting memory changes in middle age may be associated with increased susceptibility to semantic interference. Moreover, middle-aged adults performed comparably to older adults across all RD indices, indicating the recognition profile of middle-aged adults on RD indices more closely resembles that of older adults than young adults.